Screening for novel peptides specifically binding to the surface of ectopic endometrium cells by phage display - Linzhi, Yan; Dan, Cao; Arhin, Samuel Kofi; Ledan, Wang; Wenju, Li; Jieqiang, Lv (Cellular and Molecular Biology, 2018)
A 7-mer phage display library was employed to isolate novel peptides that specifically bind to ectopic endometrium in vitro. Phage display technology with biopanning and rapid analysis of selective interactive ligands between ectopic and eutopic endometrium cells was utilized. After 5 rounds of biopanning, 50 phage clones were randomly selected and analyzed by enzyme-linked immunosorbent assay and DNA sequencing. A peptide-competitive inhibition assay was performed to identify the affinity of positive phages toward ectopic endometrium cells. The most enriched polypeptide RTRLHTR showed higher affinity toward ectopic endometrium cells.The polypeptide RTRLHTR screened by phage display technology may offer a new direction for early diagnosis and treatment of endometriosis.